UPAYA MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V MELALUI MODEL ROLE PLAYING DI SD NEGERI 39 SUNGAI RAYA - Aina Diana (Lembaga Pengembangan Kinerja Dosen, 2022)
Acquisition of low student learning outcomes can be caused because teachers do not use learning methods or models that are relevant to learning material. Learning is still teacher-centered, so that students become learning objects, not subjects. As happened in class V SDN 39 Sungai Raya. Social studies learning outcomes of students are far from satisfactory and most students do not achieve KKM scores. Students do not understand the concept and meaning of the learning material presented. Therefore researchers feel the need to conduct classroom action research as an effort to improve student learning outcomes. This research was conducted at SDN 39 Sungai Raya precisely in class V using the role playing method. The purpose of this research was to see the learning process using the role playing method and to find out whether the role playing method can improve student learning outcomes. This research was conducted in two cycles, namely cycles 1 and 2. From the results of observations and learning evaluations conducted, it was concluded that the learning outcomes of class V students at SDN 39 Sungai Raya increased in the material Historical figures of the Hindu-Buddhist period, and Islam in Indonesia with the method role playing (role playing) increased in cycles I and II. Before the cycle (pre-cycle), only 7 students out of 35 students got a completeness score. An increase in learning outcomes occurred in cycle I where all students achieved KKM scores with a class average of 80 and in cycle II there was an increase with an average class value of 87. Class V student learning outcomes in Social Studies learning material Hindu-historical figures Buddhism and Islam in Indonesia can be improved by using role playing learning methods.